Environmentally friendly consumer behavior of millennials in Kazakhstan - Rybina, L.; Garkavenko, V.; Muratkyzy, K.; Kozhakhmetova, D.A. (Journal of Economic Research & Business Administration, 2024)
This research explores the environmentally friendly consumer behavior of Millennials in Kazakhstan through a quantitative approach. The study targets the pressing issue of sustainable consumption practices among this generation, which holds significant implications for environmental conservation. This study is aimed at exploration of determinants, patterns, and motivations behind environmentally friendly consumer behavior among Millennials in Kazakhstan. It seeks to identify the main factors influencing their choices, the extent to which eco-consciousness guides their decisions, and the influence of external factors, such as marketing strategies and peer influence. This research holds both scientific and practical significance contributing to the existing literature and offering insights into the emerging trends of green consumerism among Millennials in a Central Asian context. Moreover, it provides a quantitative assessment of the factors shaping their eco-friendly consumption, allowing for a nuanced understanding of their behavior. The research methodology involves the administration of structured surveys to a representative sample of Millennials in Kazakhstan. Data analysis performed with the use of such statistical methods as regression analysis and hypothesis testing to draw meaningful conclusions. Preliminary findings suggest that while environmental awareness plays a role in Millennials’ consumer choices, other factors such as affordability and convenience also significantly influence their behavior. The research underscores the need for targeted strategies to encourage more sustainable consumption practices among this demographic. In conclusion, this research contributes valuable insights into the environmentally friendly consumer behavior of millennials in Kazakhstan, shedding light on the factors driving their choices and serving as a basis for the development and implementation of effective sustainability campaigns. It has the potential to inform policymakers, marketers, and businesses seeking to align their strategies with the preferences of this eco-conscious generation. Key words: millennials, environmentally friendly consumer behavior, Kazakhstan, sustainability.